Meta-analysis of the TQM impact on business performance amongst regions and countries. (2015) - Ahmad, M.F.; Zakuan, N.; Ahmad, J.; Takala, J.
Meta-analysis has been conducted based on 20 previous works from 4, 040 firms at 16 countries from Asia, Europe and USA. Throughout this paper, the meta-analysis is applied to review the impact of TQM on business performance amongst the regions and countries. The result of meta-analysis shows that the average of regression coefficient (rc) is 0.47; Asia (rc = 0.54), USA (rc = 0.43) and Europe (rc = 0.38). Asia developed countries have the greatest impact of TQM towards business performance (rc = 0.56). ANOVA and t-test have been conducted to test the difference amongst type of country (developed and developing countries) and regions at p = 0.05. However, the result shows that there is no significant difference. In addition, rc2 of each country have been calculated based on rc value and the average result of rc2 is 0.24; Asia (rc2 = 0.33), USA (rc2 = 0.22) and Europe (rc2 = 0.15). Meanwhile, rc2 in developing countries (rc2 = 0.28) are higher than developed countries (rc2 = 0.21).